The Antropology of Alfred Kroeber as Morphological Epistemology - Osorio, José Manuel (Estudios de Filosofía, 2015)
The main thesis of the article is that Goethe’s morphology can serve as a reading guide to Alfred Kroeber’s anthropology. Specifically, the comparative study will help the reader by providing unity to Kroeber’s methodological reflections on the concepts of history and pattern in Alfred Kroeber’s oeuvre.